2020
DOI: 10.25011/cim.v43i2.34048
|View full text |Cite
|
Sign up to set email alerts
|

Crush is superior to Culotte in two-stent strategy for treatment of left main coronary artery bifurcations: A systematic review and meta-analysis

Abstract: Purpose: Crush and Culotte techniques have been used increasingly to treat patients with complex unprotected left main coronary artery bifurcation lesions. This article compares published data on these two techniques. Methods: Databases, including PubMed, Embase, Cochrane Library, Wanfang Data and China National Knowledge Infrastructure, were searched for articles published before Aug 21, 2019 to identify all relevant studies on left main coronary artery bifurcation lesions treated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In another network meta-analysis by Chiabrando et al, [24] who studied 4285 patients in 14 studies, DK crush stenting and mini-crush stenting were shown to be associated with less MACE or complications when compared to other techniques including PS. Chen et al [22] published a recent meta-analysis which also suggested the clinical benefits of lower MACE from DK crush stenting than the other 2-stent strategies.…”
Section: Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In another network meta-analysis by Chiabrando et al, [24] who studied 4285 patients in 14 studies, DK crush stenting and mini-crush stenting were shown to be associated with less MACE or complications when compared to other techniques including PS. Chen et al [22] published a recent meta-analysis which also suggested the clinical benefits of lower MACE from DK crush stenting than the other 2-stent strategies.…”
Section: Meta-analysismentioning
confidence: 99%
“…Several meta-analyses consistently demonstrated that DK crush was associated with fewer coronary events and complications than bifurcation techniques. [22][23][24][25] In a recent network meta-analysis, Di Gioia et al [23] analyzed 21 randomized studies of 5711 patients, which showed that the DK-crush stenting technique was associated with less occurrence of MACE than those treated using PS mainly driven by a reduction in TLR. More specifically, no significant differences among techniques were observed in cardiac death, MI, and stent thrombosis.…”
Section: Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations